Actinomycosis as a Rare Local Manifestation of Severe Periodontitis - Moody Kaldas; André Barghorn; Patrick R. Schmidlin (Hindawi Limited, 2020)
Actinomycosis is a chronic suppurative infection primarily caused by anaerobic gram-positive filamentous bacteria, primarily of the genus Actinomyces. Oral-cervicofacial actinomycosis is the localization found most often, presenting as a soft tissue swelling, an abscess, a mass lesion, or sometimes an ulcerative lesion. Periodontitis-like lesions, however, are rare findings. This report describes the case of a 41-year-old healthy female patient (nonsmoker), who was referred to the clinic with dull and throbbing pain in the second quadrant. Tooth 25 showed increased mobility and probing pocket depths up to 10 mm, with profuse bleeding upon probing. Radiographically, considerable interproximal horizontal bone loss was found, and the diagnosis of periodontitis stage 3, grade C was made. The situation was initially stabilized with adhesive splinting and local anti-infective therapy. Two weeks later, the bone defect was treated with guided tissue regeneration (GTR) using a xenogenic filler material (BioOss Collagen) and a resorbable membrane (Bio-Gide). Due to a suspicious appearance of the excised granulation tissue, the collected fragments were sent for histopathological evaluation. This evaluation revealed a chronic granulomatous inflammation with the presence of filamentous bacterial colonies, consistent with Actinomyces. The patient was successfully treated. While there are only few reports in the literature, actinomycotic lesions represent a rare but possible finding in cases with localized periodontal destruction. In conclusion, systematic biopsy of the infrabony tissue in localized periodontal lesions may help to provide a more accurate counting of Actinomyces-associated lesions, thereby improving diagnosis, therapy, and prevention.